Exploring the potentials of indigenous Saccharomyces cerevisiae and Pichia kudriavzevii for enhancing flavour and aromatic characteristics in apricot wines - Yu Chen; Xingmeng Lei; Luxing Sun; Binghong Gao; Peng An; Dongqing Ye; Haibin Mu; Yi Qin; Yuyang Song; Yanlin Liu (Food Chemistry: X)
In this study, we investigated the oenological performance of key yeast populations previously identified from apricot wine fermentation, aiming to obtain indigenous starters suitable for apricot wine production. Twenty-one isolates were characterized physiologically, and two isolates each of Saccharomyces cerevisiae and Pichia kudriavzevii were selected for laboratory-scale fermentations. Results showed that S. cerevisiae S9 exhibited significantly higher sugar consumption than S2 and CECA strains, with the former demonstrating a fructophilic character. Mixed fermentations of P. kudriavzevii N11 and N12 resulted in lower citric acid content (decreasing by 12–25 %) and higher glycerol levels (increasing by 12–47 %) compared to pure fermentation. In the mixed fermentation, indigenous S. cerevisiae species supported the survival of P. kudriavzevii, effectively enhancing the fruity esters and terpenes content of apricot wine. This study provides technical support for screening specialized starters for apricot wine production.